Take a Risk or Play it Safe? Views Held by Student-Athletes - Russell Ravert; Marissa Turner; Wenting Sun (Journal of Athlete Development and Experience)
Because assessing and managing risks is an integral part of sports, athletes may develop general beliefs regarding taking and avoiding risks that they draw upon. This qualitative study used inductive content analysis of survey responses to examine risk-related experiences and attitudes in sample of U.S. NCAA Division I college student-athletes (N = 101) from a variety of sports. Participants were asked to describe situations they experienced that required deciding whether or not to take risks, and to describe their “personal philosophy” on taking risks and playing it safe. Thematic analysis identified five situational contexts in which the student-athletes said they encountered risk decisions: a) during competition, b) managing health and injuries, c) preparing for competition, d) managing expectations, and e) navigating student-athlete life. Student-athletes valued taking risks for success, personal growth, avoidance of regrets, and social approval. Although most respondents were able to describe situations in which they considered it best to play safe, either as the best competitive strategy, to avoid injury/protect one’s health, and to follow instincts, a small segment of participants expressed that it is never acceptable to play it safe. Findings hold implications for coaches, trainers, parents and others working to improve student-athlete success and well-being.